FSTI researchers developed mobile and environment-friendly water treatment system - Wan Faizal, Wan Ishak; Wan Mohd Hafizuddin, Wan Yussof (Pejabat Naib Canselor, 2016)
Flood disaster that occurred each year caused a lot of problems to public amenity system – clean water supply system was compromised, electrical grid failed to function and infrastructure was damaged. All these led to water pollution in the affected, populated areas.